2008
DOI: 10.1097/01.ncc.0000305760.04357.96
|View full text |Cite
|
Sign up to set email alerts
|

The Caregiving Experience in a Racially Diverse Sample of Cancer Family Caregivers

Abstract: The literature supports a variety of predictor variables to account for the psychological and stress burden experienced by cancer family caregivers. Missing among the predictor variables are the differences by or influence of race/ethnicity. The purpose of this study was to describe the sample, explore differences in outcomes by patient and family caregiver characteristics, and determine if any of the patient and family characteristics, including race/ethnicity, predicted outcomes. Cross-sectional surveys were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 31 publications
3
52
0
1
Order By: Relevance
“…For example, caregivers of patients with multiple sclerosis reported distress related to assisting with patients' activities of daily living, assuming responsibility for coordinating healthcare resources, and providing emotional support. 17 In studies of caregivers for patients with cancer, HIV, and Alzheimer's disease, caregivers described sacrifices in their lives in relation to work, social activities, and finances 3,4,18,19 Although very few studies described caregiver experiences in the LVAD population, similar findings were reported. For example, Casida identified a theme of emotional distress characterized by guilt, fear, and anxiety.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, caregivers of patients with multiple sclerosis reported distress related to assisting with patients' activities of daily living, assuming responsibility for coordinating healthcare resources, and providing emotional support. 17 In studies of caregivers for patients with cancer, HIV, and Alzheimer's disease, caregivers described sacrifices in their lives in relation to work, social activities, and finances 3,4,18,19 Although very few studies described caregiver experiences in the LVAD population, similar findings were reported. For example, Casida identified a theme of emotional distress characterized by guilt, fear, and anxiety.…”
Section: Discussionmentioning
confidence: 86%
“…Caregiver burden, caregiver strain, grief, and clinical depression have all been characterized as components of the caregiver experience in noncardiac patient populations, including oncology, [3][4][5] geriatric with Alzheimer's disease, 3,6,7 HIV, and other chronic diseases. 3,[8][9][10] To date, few researchers have examined the experiences of family caregivers of patients requiring LVAD support.…”
mentioning
confidence: 99%
“…In addition, the DfT wanted to focus on possible differences by race and ethnicity. This decision is generally supported by a large body of work that shows racial and ethnic differences in all aspects of caregiving to older family members even holding other variables constant (Laditka and Laditka, 2001;Ramos, 2004;Sarkisian, 2004;Sander et al, 2007;White-Means and Rubin, 2008;Herrera et al, 2008;Scharlach et al, 2008;Brown, 2008), although there are also contrasting views suggesting that racial/ethnic differences disappear after controlling for socio-economic variables (see Ball et al, 2009;Siefert et al, 2008;Brown et al, 2009).…”
Section: The Study Rationalementioning
confidence: 95%
“…In all three countries, however, a moderate to high income was the next best predictor of better SAHS, an almost universal finding among health economics researchers (see Craig, 2005;Kipp et al, 2008;Macran et al, 1994;Sacker et al, 2005;Wilson, Jerret, & Eyles, 2001) where the link between income inequality and health outcomes is well established. It is only in very recent studies that the relationship between income level and caregivers' well-being is beginning to be established (Mitrani, Vaughan, McCabe, & Feaster, 2008;Papastavrou, Charalambous, & Tsangari, 2009;Siefert, Williams, Dowd, Chappel-Aiken, & McCorkle, 2008;Vellone, Piras, Talucci, & Cohen, 2008). In these studies women caregivers are more likely to be low income than their male counterparts or noncaregiving women, and older women, the most numerous group of caregivers, have the lowest income of all (Conway-Giustra et al, 2002;Kneipp, Castleman, & Gailor, 2004;Robinson, 1997).…”
Section: Discussionmentioning
confidence: 99%